Pemberdayaan Ekonomi Masyarakat di Kampung Literasi Kelurahan Karyamulya melalui Inovasi Produk Keripik Pelepah Pisang - Rani, Sasiska; Padmuji, Muhni; Pratama, Arif; Febyardalova, Febyardalova (LPPM Universitas Bumigora, 2024)
The Literacy Village in Karyamulya Village, Sematang Borang District, has so far only focused on growing local children's interest in reading. However, around Literacy Village there are many banana plants whose stems can be used to make chips. Therefore, this community service activity was carried out to expand the knowledge and foster innovation of the women who manage the Literacy Village. Apart from fostering local children's interest in reading, Literacy Village administrators can also innovate by processing useless banana stems into a product, namely banana stem chips. The banana stem chips produced can be consumed by yourself or can be marketed commercially so that it becomes a business opportunity and can improve the economy of the surrounding community. The method for implementing this service activity is by conducting observations and surveys, then providing counseling, training and assistance in making banana stem chips. The result of this service activity is that the Literacy Village administrators have been able to make banana stem chips and sell them in the surrounding area. It is hoped that this service activity can improve the economy of the surrounding community by developing MSMEs in Literacy Village through marketing products that are not only in the surrounding area but can also be marketed widely